Life Cycle Assessment of Banned Single-Use Plastic Products and Their Alternatives - Rebecca Goodrum; Bibiana Bartokova; Poritosh Roy (Microplastics)
Plastic and microplastic contamination continue to be growing problems across the globe for both ecosystems and human health. Canada has banned single-use plastic products such as bags, cutlery, and foodservice ware (containers) to address and mitigate plastics and microplastic contamination. This study evaluates the life cycle of banned plastic products and their alternatives to determine whether environmental impacts can be mitigated. The environmental impacts of bags (plastic, paper, cotton), cutlery (plastic, wooden, biodegradable), and containers (plastic, styrofoam, biodegradable) were determined considering both domestic and imported products. The bag study saw paper bags having the highest environmental impacts and cotton bags with the lowest due to their reusability. For the cutlery study, plastic cutlery was the most impactful across all categories except for eutrophication and ozone depletion, where biodegradable cutlery was the most impactful by 25% and 35%, respectively. In the case of foodservice ware (containers), styrofoam was found to be the least impactful. Similar to cutlery, the plastic containers had the greatest impact except where the biodegradable container contributed more to ozone depletion and eutrophication by 25% and 45%, respectively. Local production reduced impacts across all categories. Furthermore, on a local scale, biodegradable cutlery had a greater impact on the smog and respiratory effects categories than plastic by 10% and 30%, respectively. The results of this study indicate that future regulations should focus on promoting and educating consumers on the use of reusable products over single-use products, funding research to mitigate challenges associated with waste management, and consider an informed ban on all single-use products and not just those made of plastic material to mitigate environmental impacts.